Always a sister : - Daniels, Doris (The Feminist Press, 1989)
Always A Sister offers the inspiring biography of Lillian D Wald (1867-1940), a pioneer in the early public health movement. After founding the Henry Street Settlement and the Visiting Nursing Service in New York City, Wald went on to become a major player in the shaping of health care policies during the Progressive period. In the first biography to explore Wald's life and achievements as a public health nurse and social activist, Daniels maintains that Wald's belief in social reform was inseparable from her desire to improve the position of women. Always A Sister traces Wald's life from her early training as a nurse to her life-long lobbying for improvements on behalf of better housing, health care, and labour legislation, and her involvement in the peace movement in World War I.